2013
DOI: 10.1093/geronb/gbt028
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Activity Restriction Buffers the Relations Between Chronic Stress and Sympathetic Nervous System Activation

Abstract: The subjective experience of AR can play an important role in determining risk for detrimental physical health outcomes, particularly CVD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…As these sleep–wake behaviours were associated uniquely with subclinical depression severity in our sample, they may represent behavioural underpinnings of increased risk for major depression in strained caregivers who have subclinical depression symptoms. These findings are consistent with past studies, which have found that night‐time sleep and daytime activity are both disrupted and central to health in caregivers (Burton et al ., ; Castro et al ., ; Ho et al ., ; Mausbach et al ., , ; McKibbin et al ., ; Rowe et al ., ; Wilcox and King, ). Importantly, our study demonstrates that these behavioural markers of depression in caregivers, which occur across the entire 24‐h sleep–wake cycle, can be measured objectively with actigraphy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As these sleep–wake behaviours were associated uniquely with subclinical depression severity in our sample, they may represent behavioural underpinnings of increased risk for major depression in strained caregivers who have subclinical depression symptoms. These findings are consistent with past studies, which have found that night‐time sleep and daytime activity are both disrupted and central to health in caregivers (Burton et al ., ; Castro et al ., ; Ho et al ., ; Mausbach et al ., , ; McKibbin et al ., ; Rowe et al ., ; Wilcox and King, ). Importantly, our study demonstrates that these behavioural markers of depression in caregivers, which occur across the entire 24‐h sleep–wake cycle, can be measured objectively with actigraphy.…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, as mentioned above, past studies have characterized relationships between RARs and depression in studies that were not specific to caregivers (Hori et al ., ; Luik et al ., ; Maglione et al ., ; Robillard et al ., , ; Smagula et al ., ,b). The relationship between RARs and depression may be particularly pronounced or nuanced in dementia caregivers, in whom past literature has documented both daytime activity restriction (Burton et al ., ; Ho et al ., ; Mausbach et al ., , ) and night‐time sleep disruption (Castro et al ., ; King, 1999; McKibbin et al ., ; Wilcox Rowe et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…However, studies on family caregivers of adults show that leisure activities can reduce perceived care burden [20,21]. Moreover, leisure activities and leisure satisfaction mediate the relationship between caregiving stress and caregiver health in family caregivers of adult and elderly loved ones [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that providing informal care leads to a reduction of leisure time activities (Ory et al., ), and also to an increased risk for mental health problems (Cuijpers, ). Informal dementia caregivers engage both in fewer leisure activities overall (Ory et al., ) and less diverse leisure activities than non‐caregivers (Ho et al., ). Informal dementia caregivers have been shown to prioritise caregiving over their own leisure activities.…”
Section: Introductionmentioning
confidence: 99%